Sequencing of Australian wild rice genomes reveals ancestral relationships with domesticated rice - Brozynska, Marta; Copetti, Dario; Furtado, Agnelo; Wing, Rod A.; Crayn, Darren; Fox, Glen; Ishikawa, Ryuji; Henry, Robert J. (Wiley, 2017)
The related A genome species of the Oryza genus are the effective gene pool for rice. Here, we report draft genomes for two Australian wild A genome taxa: O. rufipogon‐like population, referred to as Taxon A, and O. meridionalis‐like population, referred to as Taxon B. These two taxa were sequenced and assembled by integration of short‐ and long‐read next‐generation sequencing (NGS) data to create a genomic platform for a wider rice gene pool. Here, we report that, despite the distinct chloroplast genome, the nuclear genome of the Australian Taxon A has a sequence that is much closer to that of domesticated rice (O. sativa) than to the other Australian wild populations. Analysis of 4643 genes in the A genome clade showed that the Australian annual, O. meridionalis, and related perennial taxa have the most divergent (around 3 million years) genome sequences relative to domesticated rice. A test for admixture showed possible introgression into the Australian Taxon A (diverged around 1.6 million years ago) especially from the wild indica/O. nivara clade in Asia. These results demonstrate that northern Australia may be the centre of diversity of the A genome Oryza and suggest the possibility that this might also be the centre of origin of this group and represent an important resource for rice improvement.